2021
DOI: 10.1016/j.molcel.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Gene architectures that minimize cost of gene expression

Abstract: In our manuscript, we characterized various mechanisms by which bacterial cells express similar levels of proteins in an efficient manner that reduces production costs in terms of energy and building block usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Frumkin et al (2017) measured the fitness effects of these random peptide-tagged GFPs in E. coli using FitSeq (Li, et al 2018). For 89 of them, Frumkin et al (2017) were able to calculate a “fitness residual” based on the deviation from the fitness expected from the level of GFP expression. Note that while this fitness residual controls for expression level, it still contains the cost of inefficient expression in addition to the fitness effect of the peptide itself.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frumkin et al (2017) measured the fitness effects of these random peptide-tagged GFPs in E. coli using FitSeq (Li, et al 2018). For 89 of them, Frumkin et al (2017) were able to calculate a “fitness residual” based on the deviation from the fitness expected from the level of GFP expression. Note that while this fitness residual controls for expression level, it still contains the cost of inefficient expression in addition to the fitness effect of the peptide itself.…”
Section: Resultsmentioning
confidence: 99%
“…Note that while this fitness residual controls for expression level, it still contains the cost of inefficient expression in addition to the fitness effect of the peptide itself. Frumkin et al (2017) found that low fitness residuals were associated with hydrophobic and expensive-to-synthesize amino acids. These findings are consistent with our own estimates of direct peptide effects, as hydrophobic amino acids tend to be order-prone (Linding, et al 2004; Angyan, et al 2012), and amino acid volume is highly correlated with synthesis cost in E. coli (Pearson’s correlation coefficient = 0.85, P = 2 × 10 −6 , cost for amino acid synthesis in E. coli taken from (Akashi and Gojobori 2002)).…”
Section: Resultsmentioning
confidence: 99%
“…This allowed us to identify two key parameters of the system, namely, the smoothed elongation rate λ 0 immediately following initiation and the minimal smoothed elongation rate λ min . Previous studies have established some association between the sequence context in the early 5 coding region and protein production levels (Frumkin et al, 2017;Boël et al, 2016;Ben-Yehezkel et al, 2015). For example, it has been shown that mRNA secondary structure in the first ∼ 16 codons (which locally decreases the elongation rate) negatively affects the translation rate in E. Coli, while no significant contribution of mRNA folding in other regions was found (Frumkin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established some association between the sequence context in the early 5 coding region and protein production levels (Frumkin et al, 2017;Boël et al, 2016;Ben-Yehezkel et al, 2015). For example, it has been shown that mRNA secondary structure in the first ∼ 16 codons (which locally decreases the elongation rate) negatively affects the translation rate in E. Coli, while no significant contribution of mRNA folding in other regions was found (Frumkin et al, 2017). By exposing α and λ 0 as the only parameters that currents in LD depend on, our analysis suggests a direct explanation for such contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations on NCS toolbox development have mainly been conducted in prokaryotes, such as E. coli and B. subtilis , where high‐throughput datasets and statistical analysis were applied. [ 3–8,37–40 ] Abundant evidence shows that both N‐terminal fragments from endogenous genes and randomly synthesized NCSs regulate gene translation levels efficiently and effectively. [ 3,4,6,8 ] However, an NCS toolbox for S. cerevisiae has not yet been developed.…”
Section: Discussionmentioning
confidence: 99%